2010
DOI: 10.1063/1.3525649
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and magnetism of transition metal doped Zn12O12 clusters: Role of defects

Abstract: Impacts of enhanced electronic correlation in anion p-orbitals on electronic structure and magnetic properties of nitrogen or carbon doped zinc oxide J. Appl. Phys. 111, 07E313 (2012) Magneto-optical spectrum of ZnO nanorods J. Appl. Phys. 111, 044305 (2012) First-principles study on electronic structures and magnetic properties of AlN nanosheets and nanoribbons J. Appl. Phys. 111, 043702 (2012) p-f hybridization in the ferromagnetic semiconductor HoN Appl. Phys. Lett. 100, 072108 (2012) Visible li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…This explains the magnetic behavior of ZnO clusters in presence of V Zn . The O-p states and the Zn-d states are the main contributors to the DOS at the E F , in line with the findings yielded by previous studies focusing on ZnO nanostructures, where V Zn was shown to introduce magnetism in an otherwise undoped ZnO system [12,19]. Figure 3 shows the electronic structure of ZnO cluster doped with Mg in three different cases, such as (a) without any additional defects (b) in presence of V O and (c) with V Z .…”
Section: Electronic and Optical Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…This explains the magnetic behavior of ZnO clusters in presence of V Zn . The O-p states and the Zn-d states are the main contributors to the DOS at the E F , in line with the findings yielded by previous studies focusing on ZnO nanostructures, where V Zn was shown to introduce magnetism in an otherwise undoped ZnO system [12,19]. Figure 3 shows the electronic structure of ZnO cluster doped with Mg in three different cases, such as (a) without any additional defects (b) in presence of V O and (c) with V Z .…”
Section: Electronic and Optical Propertiessupporting
confidence: 90%
“…For the dopant transition metal atom, the onsite d-d Coulomb exchange interactions were described using U = 4.0 eV and J = 1.0 eV, while the parameters U = 7.0 eV and J = 0.75 eV were adopted for the Eu atom. The choice of Hubbard parameters are taken from standard literature where reliable results are produced with these values [12]. Further, For the Eu atom, we have tested different U and J combinations and used the values that could reproduce experimental values reliably.…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The endohedral bi-doped isomer, however, is found to be a stable local minimum. The structural and magnetic properties of (ZnO) 12 nanoclusters substitutionally doped with 3d transition-metals were also studied theoretically [17]. It was found that doping of TM at the Zn site is energetically more favorable than doping it at O site.…”
Section: Introductionmentioning
confidence: 99%
“…We note that Zn(II) and Mg(II) are diamagnetic ions and that they should not display a behavior consistent with ferromagnetic ordering, albeit, as we note, this effect was slight. Otherwise, recent studies for Zn n O n clusters and ZnO nanoparticles indicated the defect induced magnetism in ZnO clusters even without any transition metal dopants [55,56]. The extrapolation of these results to the reported MOF systems can suggest the impact of the defects in MOF structures to achieve and explain the origin of magnetic properties of the reported materials.…”
Section: Ferromagnetic Ordering Behavior: Little Field Dependence On mentioning
confidence: 68%